Implementasi Sistem Pembelajaran Daring dalam Meningkatkan Kedisiplinan Belajar Aqidah Akhlak masa Pandemi Covid 19 Santri Kelas VII SMP Islam Ar-Riyad Hidayatullah Bontang Tahun Pembelajaran 2020/2021 - Zaman, Muhammad Fachrus; Ridwan, Ridwan (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This study examines the implementation of an online learning system to improve the learning discipline of Aqidah Akhlak during the COVID-19 pandemic for seventh-grade students at SMP Islam Ar-Riyadh Hidayatullah Bontang. The research aims to understand how the distance learning system was implemented and the measures taken by teachers to enhance learning discipline. Employing a qualitative approach through observation, interviews, and documentation, the findings reveal that the Aqidah Akhlak teacher plays a pivotal role in creating an engaging learning atmosphere, which significantly contributes to instilling discipline among students. The use of applications such as WhatsApp, Google Forms, Classroom, and Zoom Cloud supports discipline in attending lessons, completing assignments, and submitting tasks on time. Despite challenges and mixed reactions to the implementation, the study highlights that innovation in education can drive success if accompanied by a readiness to adapt and evolve.